Handbook of research methods and applications in economic geography [electronic resource] / edited by Charlie Karlsson, Martin Andersson and Therese Norman. (Cheltenham : Edward Elgar Pub. Ltd., 2015., 2018)
1 online resource (xii, 648 p.) : ill., maps ; cm.